Ketuhanan, kenabian dan kebahagiaan menurut Ibn Sina - Idris Zakaria, (Penerbit Universiti Kebangsaan Malaysia, 2010)
This article focuses on the concepts of God, prophethood and happiness which are among the prominent topics among many philosophers especially Muslim philosophers. These three topics become so important because they refer the main principles and pillars for the whole structure of Muslim philosophical thought. Ibn Sina (370/890-428/1037) is one of the outstanding Muslim philosophers who discussed these topics in his works such as al-Shifa, al-Najat and al-Isharat wa al-Tanbihat. The divinity discusses God’s absolute existence and His relationship with other existences; the prophethood discusses the functions of a prophet in calling human beings to believe in God’s existence and oneness and to guide them to achieve the happiness in this world and in the hereafter. Therefore, the discussion of these three topics simultaneously becomes important.